3 Can mortality be predicted for people with multiple long-term conditions – multimorbidity?. (14th March 2023) - Westhead, Elizabeth; Dewhurst, Felicity; Hanratty, Barbara
Abstract : Background: Death is now an event of older age, and living with multiple long-term conditions – multimorbidity (MLTC-M) is now the norm in later life. People dying with MLTC-M report the same symptoms as people dying with cancer yet are seldom referred to specialist palliative care services. There is no consensus on how to identify people with MLTC-M approaching the end-of-life. Aim: To synthesise evidence on identification of older people with MLTC-M approaching the end-of-life. Methods: A systematic review with narrative synthesis was conducted. The review protocol was registered prospectively with PROSPERO (CRD:42022324986). Databases searched: Medline, CINAHL, EMBASE, Psychinfo and Scopus. Databases were searched for studies published during or after 2002, until 4th March 2022. Quality was assessed using NIH Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. The population studied were adults >50 years old, with MLTC-M. The exposures of interest were prognostic tools based on weighted indices. The outcome of interest was prognostic ability of the weighted index studied. Results: 8479 articles were identified and screened. 28 studies were included, all of observational design. 7 tools based on weighted indices were identified: Charlson Comorbidity Index, Elixhauser Comorbidity Index, Charlson-Deyo Comorbidity Index, Multimorbidity Weighted Index- ICD-10, Cumulative Illness Rating Scale and Disease Burden Morbidity Assessment. Of the tools identified, the Charlson Comorbidity Index had the largest evidence base, and performed best. A higher score Charlson Comorbidity score was associated with increased likelihood of death within the next 12 months. Conclusion: This review provides healthcare professionals with an evidence-based assessment for prognosticating at the end-of-life for people with MLTC-M. This will inform advance care planning, treatment decisions and service provision for those with MLTC-M. Identification of people with MLTC-M nearing the end-of-life will facilitate the management of their symptoms, and improve their end-of-life care experiences.